Cody

# Problem 43. Subset Sum

Solution 1977952

Submitted on 15 Oct 2019 by Alvin LAU
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

### Test Suite

Test Status Code Input and Output
1   Pass
v = [2, 3, 5]; n = 8; correct = [2, 3]; actual = subset_sum(v, n); assert(isequal(actual, correct))

d = 0 0 1 d = 0 1 0 d = 0 1 1 ind = 2 3 d = 1 0 0 d = 1 0 1 d = 1 1 0 d = 1 1 1

2   Pass
v = [5, 3, 2]; n = 2; correct = 3; actual = subset_sum(v, n); assert(isequal(actual, correct))

d = 0 0 1 ind = 3 d = 0 1 0 d = 0 1 1 d = 1 0 0 d = 1 0 1 d = 1 1 0 d = 1 1 1

3   Pass
v = [2, 3, 5]; n = 4; correct = []; actual = subset_sum(v, n); assert(isequal(actual, correct))

d = 0 0 1 d = 0 1 0 d = 0 1 1 d = 1 0 0 d = 1 0 1 d = 1 1 0 d = 1 1 1

4   Pass
v = [1, 1, 1, 1, 1]; n = 5; correct = [1, 2, 3, 4, 5]; actual = subset_sum(v, n); assert(isequal(actual, correct))

d = 0 0 0 0 1 d = 0 0 0 1 0 d = 0 0 0 1 1 d = 0 0 1 0 0 d = 0 0 1 0 1 d = 0 0 1 1 0 d = 0 0 1 1 1 d = 0 1 0 0 0 d = 0 1 0 0 1 d = 0 1 0 1 0 d = 0 1 0 1 1 d = 0 1 1 0 0 d = 0 1 1 0 1 d = 0 1 1 1 0 d = 0 1 1 1 1 d = 1 0 0 0 0 d = 1 0 0 0 1 d = 1 0 0 1 0 d = 1 0 0 1 1 d = 1 0 1 0 0 d = 1 0 1 0 1 d = 1 0 1 1 0 d = 1 0 1 1 1 d = 1 1 0 0 0 d = 1 1 0 0 1 d = 1 1 0 1 0 d = 1 1 0 1 1 d = 1 1 1 0 0 d = 1 1 1 0 1 d = 1 1 1 1 0 d = 1 1 1 1 1 ind = 1 2 3 4 5

5   Pass
v = [1, 2, 3, 4, 100]; n = 100; correct = 5; actual = subset_sum(v, n); assert(isequal(actual, correct))

d = 0 0 0 0 1 ind = 5 d = 0 0 0 1 0 d = 0 0 0 1 1 d = 0 0 1 0 0 d = 0 0 1 0 1 d = 0 0 1 1 0 d = 0 0 1 1 1 d = 0 1 0 0 0 d = 0 1 0 0 1 d = 0 1 0 1 0 d = 0 1 0 1 1 d = 0 1 1 0 0 d = 0 1 1 0 1 d = 0 1 1 1 0 d = 0 1 1 1 1 d = 1 0 0 0 0 d = 1 0 0 0 1 d = 1 0 0 1 0 d = 1 0 0 1 1 d = 1 0 1 0 0 d = 1 0 1 0 1 d = 1 0 1 1 0 d = 1 0 1 1 1 d = 1 1 0 0 0 d = 1 1 0 0 1 d = 1 1 0 1 0 d = 1 1 0 1 1 d = 1 1 1 0 0 d = 1 1 1 0 1 d = 1 1 1 1 0 d = 1 1 1 1 1

6   Pass
v = [-7, -3, -2, 8, 5]; n = 0; correct = [2, 3, 5]; actual = subset_sum(v, n); assert(isequal(actual, correct))

d = 0 0 0 0 1 d = 0 0 0 1 0 d = 0 0 0 1 1 d = 0 0 1 0 0 d = 0 0 1 0 1 d = 0 0 1 1 0 d = 0 0 1 1 1 d = 0 1 0 0 0 d = 0 1 0 0 1 d = 0 1 0 1 0 d = 0 1 0 1 1 d = 0 1 1 0 0 d = 0 1 1 0 1 ind = 2 3 5 d = 0 1 1 1 0 d = 0 1 1 1 1 d = 1 0 0 0 0 d = 1 0 0 0 1 d = 1 0 0 1 0 d = 1 0 0 1 1 d = 1 0 1 0 0 d = 1 0 1 0 1 d = 1 0 1 1 0 d = 1 0 1 1 1 d = 1 1 0 0 0 d = 1 1 0 0 1 d = 1 1 0 1 0 d = 1 1 0 1 1 d = 1 1 1 0 0 d = 1 1 1 0 1 d = 1 1 1 1 0 d = 1 1 1 1 1